Phase II trial of gemcitabine and nab‐paclitaxel in patients with recurrent Ewing sarcoma: A report from the National Pediatric Cancer Foundation. Issue 7 (9th May 2020) - Oesterheld, Javier E.; Reed, Damon R.; Setty, Bhuvana A.; Isakoff, Michael S.; Thompson, Patrick; Yin, Hong; Hayashi, Masanori; Loeb, David M.; Smith, Tiffany; Makanji, Rikesh; Fridley, Brooke L.; Wagner, Lars M.
Abstract: Background: The combination of gemcitabine and docetaxel is often used to treat patients with recurrent sarcoma. Nab‐paclitaxel is a taxane modified to improve drug exposure and increase intratumoral accumulation and, in combination with gemcitabine, is standard therapy for pancreatic cancer. Applying the dosages and schedule used for pancreatic cancer, we performed a phase II trial to assess the response rate of gemcitabine and nab‐paclitaxel in patients with relapsed Ewing sarcoma. Procedure: Using a Simon's two‐stage design to identify a response rate of ≥ 35%, patients received nab‐paclitaxel 125 mg/m 2 followed by gemcitabine 1000 mg/m 2 i.v. on days 1, 8, and 15 of four‐week cycles. Immunohistochemical analysis of archival tissue was performed to identify possible biomarkers of response. Results: Eleven patients from four institutions enrolled, with a median age of 22 years (range, 14‐27). Patients were heavily pretreated (median 3 prior regimens, range, 1‐7). Thirty‐five cycles were administered (median 2, range, 1‐8). Accrual was stopped after 11 patients, due to only one confirmed partial response. Two other patients had partial responses after two cycles, but withdrew because of adverse effects or progression before confirmation of continued response. The predominant toxicity was myelosuppression, and four (36%) patients were removed due to hematologic toxicity despite pegfilgrastim and dose reductions. Expression of secreted protein, acidic and rich in cysteine (SPARC) and CAV‐1 in archival tumors was not predictive of clinical benefit in this small cohort of patients. Conclusions: In patients with heavily pretreated Ewing sarcoma, the confirmed response rate of 9% was similar to multi‐institutional studies of gemcitabine and docetaxel.